2006
DOI: 10.1097/01.mph.0000212960.66221.e7
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Associated Hodgkin Lymphoma in a 9-Year-Old Girl Receiving Long-Term Methotrexate Therapy for Juvenile Idiopathic Arthritis

Abstract: We describe a case of Hodgkin lymphoma developing in a 9-year-old girl with polyarticular, rheumatoid factor-positive juvenile idiopathic arthritis treated with methotrexate (MTX), prednisone, and naproxen for 5 years. Pathologic and molecular analyses revealed that the Hodgkin cells contained Epstein-Barr virus and the viral DNA was monoclonal. She achieved complete remission after MTX withdrawal, chemotherapy, and radiation. To the best of my knowledge, this is the sixth report of Hodgkin lymphoma in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Further, some cases of lymphoma are reported in JIA patients treated with MTX and other immunosuppressants, some of them EBV-associated (8). Three cases have been reported where JIA patients developed lymphoma after combination therapy of MTX and etanercept and with other immunosuppressants in two of the cases (9).…”
Section: Discussionmentioning
confidence: 99%
“…Further, some cases of lymphoma are reported in JIA patients treated with MTX and other immunosuppressants, some of them EBV-associated (8). Three cases have been reported where JIA patients developed lymphoma after combination therapy of MTX and etanercept and with other immunosuppressants in two of the cases (9).…”
Section: Discussionmentioning
confidence: 99%
“…Awareness of a past or current EBV infection has been shown to be beneficial in determining treatment options for patients with certain rheumatic diseases. As noted in this review, JIA patients treated with MTX may lead to mishandling of EBV by T cells [17,18]. Additionally, EBV-infected ITP patients demonstrated a slower remission rate following treatment with steroids [28].…”
Section: Resultsmentioning
confidence: 82%
“…Recently, it was reported that a 9-year-old girl with a 7-year history of IgM rheumatoid factor (RF)-positive polyarticular JIA had been treated with methotrexate (MTX) and later developed nodular sclerosing Hodgkin lymphoma [17]. She had IgG EBV antibodies, while IgM EBV antibodies were negative.…”
Section: Juvenile Idiopathic Arthritis (Jia)mentioning
confidence: 99%
“…Although rare, MTX has been reported to induce hypersensitivity pneumonitis 88 and Hodgkin lymphoma associated with Epstein-Barr virus. 89 MTX is also known to cause dermatologic side effects such as oral ulcers, urticaria, alopecia, and cutaneous nodules.…”
Section: ' Treatmentmentioning
confidence: 99%